Effectiveness of Internships Bridging Education and Industry: An Evaluation Based an a Qualitative Study - Dimas Yoga Prasetya; Chandra Fitra Arifianto; Ading Sunarto (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
Internships are believed to be an appropriate way to bridge education with the world of work, or link and match. This study focuses on the effectiveness of internships in higher education. This type of qualitative research takes the form of a case study, which aims to obtain an in-depth exploration of events. Informants were determined using a purposive sampling technique based on certain characteristics deemed relevant to the research objectives, resulting in the involvement of five informants and one key informant. Data collection was obtained through interviews and observations supported by other data. Data analysis was conducted descriptively qualitatively through the stages of reduction, presentation, and drawing conclusions, followed by data triangulation. The results of the study indicate that three main indicators task relevance, supervision quality, and institutional support comprehensively explain the conditions experienced by informants. Specifically, internship programs have proven effective in strengthening soft skills such as communication, teamwork, adaptability, and self-confidence; enhancing job readiness through experiences facing real-world challenges and organizational culture; and fostering a professional ethos. Thus, this study provides a theoretical contribution by strengthening the framework for internship effectiveness, as well as a practical contribution in the form of recommendations for universities and industry partners to design internship programs that are more structured, relevant, and aligned with students' fields of study and the needs of the workplace.